Micro-RNA-371a-3p in Germ Cell Testicular Tumors on Diagnosis: A Prospective Case-Control Study in Turkish Population - Kılınç, Muzaffer Tansel; Göger, Yunus Emre; Özkent, Mehmet Serkan; Kılıç, Özcan; Okur Altındaş, Betül; Yıldırım, Mahmut Selman; Karalezli, Giray (Urology Journal, 2024)
Purpose: We aimed to evaluate the diagnostic sensitivity and specificity of the miRNA-371a-3p for the primary diagnosis of germ cell tumors (GCT) and to investigate its relationship with pathological factors and clinical stage in the Turkish population. Materials and Methods: In this prospective study, a total of 60 patients with GCTs, and 40 healthy male controls were examined for serum levels of miRNA-371a-3p before orchiectomy and again two weeks after surgery. The miRNA-371a-3p, alpha-fetoprotein (AFP), and beta-human chorionic gonadotropin (bHCG) levels in the preoperative and postoperative periods were compared at different clinical stages. Receiver operating characteristics curve analyses were performed to determine the sensitivity and specificity of miRNA-371a-3p. Clinical and pathological factors such as clinical stage (CS), tumor size, histology, rete testis invasion, and lymphovascular invasion, potentially impacting miRNA-371a-3p expression levels (relative quantity, RQ), were evaluated statistically. Results: The sensitivity of miR-371a-3p in GCT patients was 98.3%, and the specificity was 95% (AUC = 0.997 [95%Cl:0.99–1], p < .001). miR-371a-3p expression was not detected in two patients with teratoma. The median miR-371a-3p RQ was 489 times in GCT and 2.2 times in the Control group (p < .001). In the postoperative period, there was a significant decrease in AFP and bHCG levels in all CS-1 (p = .01) and 30% of the other CS (p = .3). Throughout this time there was a decrease of 19 times at the miR-371a-3p RQ in CS-1(p < .001) and 1.6 times in the other CS (p < .001). The miR-371a-3p RQs were correlated with tumor size and CS. Conclusion: The miR-371a-3p seems to have higher diagnostic accuracy than classical serum tumor markers in GCT.